Pengelolaan Parkir di Kabupaten Brebes - Nia Elfiani Purba; Turtiantoro -; Wahid Abdurrahman (Journal of Politic and Government Studies, 2018)
Parking is an empty land provided by the Regional Government to park motor vehicles. Local Government provides parking areas for the users of vehicles who want to park their vehicles to reduce traffic jam. Parking officers prepared by the Department of Transportation as a manager to collect tariffs from the users of the parking area, but they did not provide the ticket as a proof of transaction. The action opens an opportunity for parking officers to attract more expensive parking fees from users that does not match the nominal listed. It also opens an opportunity for motor or helmet theft. In addition, the lack of parking area provided by the Local Government caused many parking users park their vehicles outside parking area and causing traffic jam.This research used qualitative explorative research method by collecting data using interview, observation and documentation, so that it can explain the real situation. Infomant of this study are officers from the Department of Transportation of Brebes Regency, the officers from Brebes District Revenue and Financial Service Department, the Parking Officer and the public.The results of this study shows that the parking management in Brebes regency still has not reached the expected goal because the achievement of parking fees that are collected still not reached the target set by the Local Government caused by several factors and the achievement of parking tax also fluctuate. The use of Self Assessment system on the parking tax give an opportunity for Taxpayers to cheat who only hold on to trust. The Local Government, the Department of Transportation and the Revenue and Finance Service Office of Brebes Regency must cooperate in order to solve the problems. They can take action such increasing parking areas, taking decisive action against parking officers who do not give tickets, and conduct strict control to the Taxpayer.Keywords: Parking, Parking Management, Parking Officer, Taxpayer